2008
DOI: 10.1198/004017007000000353
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Based Methods for a Gamma Distribution

Abstract: In this article we propose inferential procedures for a gamma distribution using the Wilson-Hilferty (WH) normal approximation. Specifically, using the result that the cube root of a gamma random variable is approximately normally distributed, we propose normal-based approaches for a gamma distribution for (a) constructing prediction limits, one-sided tolerance limits, and tolerance intervals; (b) for obtaining upper prediction limits for at least l of m observations from a gamma distribution at each of r loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…As we can see, our proposed methods perform quite well in regardless of different settings. It is worth mentioning that the normal-based method for a gamma distribution proposed in [15] actually does not work very well for the one-sided tolerance limit case. In their study, the coverage probabilities for the upper tolerance limit are uniformly smaller than the nominal values.…”
Section: Simulation Studymentioning
confidence: 99%
See 3 more Smart Citations
“…As we can see, our proposed methods perform quite well in regardless of different settings. It is worth mentioning that the normal-based method for a gamma distribution proposed in [15] actually does not work very well for the one-sided tolerance limit case. In their study, the coverage probabilities for the upper tolerance limit are uniformly smaller than the nominal values.…”
Section: Simulation Studymentioning
confidence: 99%
“…In this section, we use the same data set in [15] for illustrative purpose. This data set in Table III represents Table I the alkalinity concentrations in groundwater.…”
Section: Illustrative Examplementioning
confidence: 99%
See 2 more Smart Citations
“…Hinkley 1977), and the option for negative numbers is a crucial advantage. The precedent for a power transformation of negative numbers is the cube root, which is defined for negatives and normalizes the gamma-distribution (Krishnamoorthy et al 2008). We explored powers between 0.3 and 0.5, maintaining negatives, and found that the exponent 0.45 was most effective at reducing skewness; the cube-root overtransformed, and produced skewness in the opposite direction.…”
Section: Growth Modelmentioning
confidence: 99%